2022
DOI: 10.3389/fimmu.2022.910490
|View full text |Cite
|
Sign up to set email alerts
|

Lighting a Fire: Gasdermin-Mediated Pyroptosis Remodels the Glioma Microenvironment and Promotes Immune Checkpoint Blockade Response

Abstract: Pyroptosis is a proinflammatory programmed cell death pathway mediated by gasdermins. Exploring the role of pyroptosis can provide new insights into tumor malignancy. The most recent studies on pyroptosis have focused on tumor cells. However, the effects of pyroptosis on the tumor microenvironment (TME), immunotherapeutic responses, and efficacy have been neglected, especially in case of glioma. In this study, four independent glioma cohorts comprising 1,339 samples and a pan-cancer cohort comprising 10,535 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…As the most common malignant tumor in the central nervous system, glioma has a very poor prognosis ( 126 ). Pyroptosis induced by GSDMD and NLRC4 in high-grade gliomas can promote the progression of gliomas and enhance the sensitivity of these tumors to immune checkpoint therapy by recruiting immune cells ( 127 ). The inflammatory immune microenvironment induced by pyroptosis can promote the invasion and proliferation of glioma stem cells and is also related to the infiltration of M2 pheno-type bone marrow-derived macrophages (BMDMs) ( 72 , 128 ).…”
Section: The Expression Of Gsdm and Clinical Significance In Tumor Im...mentioning
confidence: 99%
See 1 more Smart Citation
“…As the most common malignant tumor in the central nervous system, glioma has a very poor prognosis ( 126 ). Pyroptosis induced by GSDMD and NLRC4 in high-grade gliomas can promote the progression of gliomas and enhance the sensitivity of these tumors to immune checkpoint therapy by recruiting immune cells ( 127 ). The inflammatory immune microenvironment induced by pyroptosis can promote the invasion and proliferation of glioma stem cells and is also related to the infiltration of M2 pheno-type bone marrow-derived macrophages (BMDMs) ( 72 , 128 ).…”
Section: The Expression Of Gsdm and Clinical Significance In Tumor Im...mentioning
confidence: 99%
“…The inflammatory immune microenvironment induced by pyroptosis can promote the invasion and proliferation of glioma stem cells and is also related to the infiltration of M2 pheno-type bone marrow-derived macrophages (BMDMs) ( 72 , 128 ). In the future, it is necessary to construct a GSDMD-deficient mouse model to probe the effects of pyroptosis as a drug target on gliogenesis and the tumor immune microenvironment ( 72 , 127 ).…”
Section: The Expression Of Gsdm and Clinical Significance In Tumor Im...mentioning
confidence: 99%
“…Among various therapeutic modalities, pyroptosis as a type of inflammatory programmed cell death has the powerful capacity to induce robust ICD, which is executed by the proteolytic cleavage of gasdermin (GSDM) family proteins. , Under the cleavage of specific caspases and proteases, GSDM proteins produce a necrotic N-terminal domain capable of plasma membrane perforation, leading to a swift plasma membrane rupture and the release of DAMPs and proinflammatory cytokines . It is documented that pyroptosis as a recently identified form of ICD has the potential to maximize the ICB response rate for a robust and durable antitumor response in both preclinical tumor models and clinical cancer patients. For instance, the Lieberman group found that granzyme B (GZMB) secreted by tumor-infiltrating natural killer (NK) and CD8 + T lymphocytes could cleave gasdermin E (GSDME) to induce pyroptosis of cancer cells, resulting in enhanced antitumor immunity . However, the GSDM expression was downregulated in most cancer types, thus limiting the efficacy of triggering pyroptosis for antitumor immunity .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used naming rules of databases and classified LGG as grade 2 and 3 glioma, HGG as grade 4 glioma. A variety of cell death modes have been confirmed to be present in glioma and participate in the tumor microenvironment (TME) (Cai et al, 2022;Liu et al, 2022). Cuproptosis may play a role in glioma development and progression of glioma.…”
Section: Introductionmentioning
confidence: 99%